Behavioral and psychophysiological effects of the physical work environment. Research strategies and measurement methods. - Gamberale, Francesco; Kjellberg, A; Åkerstedt, Torbjörn; Johansson, Gun (Scandinavian Journal of Work, Environment & Health, 1990)
An international course on the behavioral and psychophysiological effects of the physical work environment was held in Stockholm, Sweden, in April 1988 by the Nordic Institute of Advanced Training in Occupational Health and the Swedish National Institute of Occupational Health. It dealt primarily with the behavioral and psychophysiological responses to aspects of the physical work environment and was devoted to neural and behavioral functions. The increasing interest in these functions is mainly motivated by the involvement of the central nervous system in the adverse effects induced by unfavorable environmental conditions of the workplace and by the need for more sensitive indicators than those based solely on recognized occupational disease and pathology. By describing the main aspects of the research strategies and the measurement methods used in this field of research, this paper provides a background for the assessment and evaluation of the early behavioral and psychophysiological indices of potential occupational hazards.